Film editing : history, theory and practice : looking at the invisible / Don Fairservice. - Fairservice, Don (Manchester University Press, 2001)
This examination of the film editor's craft ranges from the beginning of cinema to the 21st century. Film editing is the least understood of the cinematic crafts. This book explains not only the how but also the why of this film making activity.